Aerosol Production During Blood and Urine Pre-analytical Processing and Handling in a Hospital Biochemistry Clinical Laboratory During the COVID-19 Pandemic - Dubuis, Marie-Eve; Duchaine, Caroline (Frontiers in Public Health, 2021)
The SARS-CoV-2 pandemic has created a troublesome issue for employees in biochemistry clinical laboratories due to fears of aerosol generation during sample treatment. This study was designed to assess aerosol production during the pre-analytical procedures for blood and urine samples using a model bacterium. Air sampling and surface swabbing were conducted during four typical procedures. Bacteria were not recovered in any air or surface samples. Other studies have reported low and undetectable SARS-CoV-2 RNA in blood and urine samples, respectively. Therefore, the occupational risk for employees appears to be low in terms of aerosol exposure from processing SARS-CoV-2 patient samples.